Construction and Repair of Water Wells with Circulation Regeneration System - I. I. Ivashechkin; P. A. Avtushko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a new design of a water well with an integrated circulation and reactant regeneration system. Water well drilling technique, its maintenance and modernization have been given in the paper. The paper presents expressions for calculation of static heave while extracting a filter and a column and a corresponding example.